2023
DOI: 10.1681/asn.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Treatment Effects of Intensive Glycemic Control on Kidney Microvascular Outcomes and Mortality in ACCORD

Vivek Charu,
Jane W. Liang,
Glenn M. Chertow
et al.

Abstract: Objective: Clear criteria to individualize glycemic targets in patients with type II diabetes are lacking. In this post-hoc analysis of the Action to Control Cardiovascular Risk in Diabetes trial (ACCORD), we evaluate whether the kidney failure risk equation (KFRE) can identify patients for whom intensive glycemic control confers more benefit in preventing kidney microvascular outcomes. Research design and methods: We divided the ACCORD trial population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Study authors claimed findings of HTE in 15 risk modeling reports (Figure 2). For six, (49,60,64,71,75,77) heterogeneity was found on the absolute but not the relative scale (i.e., benefit magnification) and for nine (36,38,43,48,50,54,58,68,73), heterogeneity was also found on the relative scale (i.e., relative treatment effects also varied across levels of baseline risk). The four remaining reports (56,57,61,76) did not find clear overall treatment effects and none claimed HTE on either scale.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Study authors claimed findings of HTE in 15 risk modeling reports (Figure 2). For six, (49,60,64,71,75,77) heterogeneity was found on the absolute but not the relative scale (i.e., benefit magnification) and for nine (36,38,43,48,50,54,58,68,73), heterogeneity was also found on the relative scale (i.e., relative treatment effects also varied across levels of baseline risk). The four remaining reports (56,57,61,76) did not find clear overall treatment effects and none claimed HTE on either scale.…”
Section: Resultsmentioning
confidence: 95%
“…Table 3 gives the decision thresholds for important subgroup differences in treatment recommendations. Reasons for concluding that credible HTE was not clinically important included lack of clarity in presentation of findings, (75) failure to identify a threshold for differing treatment choices, (64) conflicting findings across outcomes, (77) failure to add clinical value to previous risk-based selection strategies, (68) and concurrence with authors on the need for additional investigation, possibly testing additional potential effect modifiers. (44)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive glycemic control leading to severe hypoglycemia has been associated with increased mortality rates ( 9 ). The international consensus on TIR ( 26 ) indicated that although evidence regarding TIR for older or high-risk individuals is limited, several studies have demonstrated an elevated risk for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…These associations between diabetes and worse outcomes in COVID-19 patients were incontrovertible, as blood glucose fluctuation was not conducive to the improvement of disease, and inflammation caused by hyperglycemia led to increased mortality ( 7 , 8 ). However, excessively tight glycemic control may increase the risk of hypoglycemia, which also increased mortality ( 9 ).The impact of COVID-19 on the patients and the use of glucocorticoids and nutritional support during the treatment increased blood glucose fluctuations, which had adverse effects on the prognosis ( 10 ). The UK Diabetes guidelines recommend a blood glucose target of 110 to 180mg/dL for diabetes patients with COVID-19, and a blood glucose level of less than 220mg/dL for patients with hypoglycemia and high risk factors (including the elderly, patients with low body weight, patients with severe COVID-19 and/or renal impairment) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%